Productivity and energy efficiency of three tillage systems for maize (Zea mayz L.) production - Jaime Ruiz-Vega; Niurka Mena-Mesa; Fidel Diego-Nava; Miguel Herrera-Suárez (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
The amount of inputs and dry matter yields of grain, stover and weeds were quantifi ed in six sites located in the districts of Zaachila and Etla, in the Central Valleys of Oaxaca Region, México. The tillage systems evaluated, which are the most widely used for corn production in this region, were full animal traction (FAT), mixed traction (MXT) and mechanical traction (MT). The higher productivity was achieved in the MT system, followed by the MxT system. According to the energy balance, the largest energy effi ciency (EE) was achieved in the FAT system with a value of 34.4 and the least one with the MT system. The lowest EE of the MT system was associated to a higher use of machinery operations and the use of petrol derivate products. No signifi cant differences in EE were found between the FAT and MxT systems; when the weed’s dry matter production was considered, EE in this last system was increased 14%, while in the FAT system an 8% increase was observed. Therefore, besides the FAT system, MxT is also recommended because it is common to have plots smaller than 1 ha in the region and mechanical plowing is more effi cient for primary tillage operations, while animal power can be used as a renewable source of energy for tasks such as weeding and transport.